Focusing aid on Africa’s own priorities - Ernest Harsch (Africa Renewal, 2005)
When the government of the African island nation of Madagascar decided last year to apply for assistance under the US’s new supplementary aid programme, the Millennium Challenge Account, it chose to break with standard practice. Instead of simply asking government ministries to suggest potential projects, the Malagasy authorities consulted civil society groups, local businesses and farmers’ associations. They encountered two recurrent complaints from farmers and small-scale businesspeople: that it is very difficult to get either bank loans or official titles to land.